Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:• Multi-Dimensional Strategic Model to Enhance Institutional Performance Under Digital Transformation: An Applied Framework in the Saudi ContextMs. Mona Jeza Almutairi , Mr. Hassan Khidhr Alhallafi,  Mr. Almotasim Khalil Alabbas• The Role of Strategic Management in Achieving Administrative Creativity at Prince Sattam University in Al-Kharj Governorate from the Perspective of Administrative EmployeesMs. Kholoud Ghaleb Mubarak Al-Dosari• Digital Transformation in Government Services: Enhancing Efficiency, Accessibility, and Citizen Experience: A Case Study of The United Arab Emirates (UAE)Dr. Khawla Mossa Abdulla AlHaiyas• Evaluating the Transformations of the Bura Biosphere Reserve in Yemen: A reading of the Environmental, Social, and Economic ContextAsst-Prof. Bardees Taher Al-Okab• The Financial Management of Stock in the Path of Allah in Achieving Economic Stability and SecurityAsst-Prof. Hazem Mahmoud Alwadi• Liquidity and Leverage Effects on Sudatel’s Financial Performance (2015–2024)Dr. Najla Fateh Elrhman Elgadi• The Contribution of Soft leadership Skills on Organizational Change: A Study on Sudanese Insurance CompaniesCo-Prof. Mohammed Mukhtar Ibrahim , Asst-Prof. Adam Yagoub Abker
Keywords: The Journal of Economic, Administrative and Legal Sciences